Novas perspectivas para o Programa de Alimentação do Trabalhador e Dieta de Saúde Planetária no Brasil na era Antropocênica - Miller, Tânia Corrêa (2023)
It is widely recognized that the global food system is unsustainable, especially after the industrialization of agriculture, which is currently based on neoproductivism. A multidisciplinary team, the EAT-Lancet Commission, composed of experts from different fields of health, agricultural, as well as, political and environmental scientists, has developed global scientific targets for the sustainable production of healthy food and diets, the so-called Planetary Health diet, based on the best available evidence. In this context, the objective of this study was to investigate the qualitative and quantitative aspects of the Planetary Health Diet and to propose a gradual adaptation for the Brazilian population, particularizing the area of Nutrition in Collective Feeding, with emphasis on the Workers' Food Program. This research belongs to the area of science, technology, and society and has an exploratory and comparative character, using the method of bibliographic and documentary research, with approaches to texts and books from the perspective of Bruno Latour and Ailton Krenak in dialog with other authors. The authors challenge us to develop other forms of modus operandi to face the “ecological mutation” in the New Climate Regime with greater clarity. From this perspective, the intersections of Nutrition science in the 21st century are identified, with the idea of reorientation to the vector that Latour calls “Terrestrial”, as a new political actor in the Anthropocene period. The comparative analysis of the Planetary Health diet and personal food consumption in Brazil revealed a high consumption of beef, lamb, and added sugars and a low consumption of fruit, vegetables, added fats, and oilseeds. As a result, an adaptation of this diet was proposed for the Brazilian population, based on the current guidelines of the Food Guide, highlighting the need to buy food from sustainable systems of production to feed workers, as well as updating the nutritional requirements of the Workers' Food Program. Given the current scenario, where everything is making us rethink our own existence on the planet, there is an urgent need to realign food systems and food consumption. The main challenge is to develop public policies that are compatible with the goals of sustainability to ensure food and nutrition security, with the responsible participation of all. Policymakers, public health professionals, nutritionists, scientists from the environmental and human fields, and civil society can form a transdisciplinary working group for decision-making resulting in develop evidence-based policy. It is expected that this research can contribute to nutrition increasingly becoming the subject of interdisciplinary scientific research in the fields of science, technology, and society.